Chemical weapons attacks: the end of anonymity : organisation for the prohibition of chemical weapons to identify perpetrators - Meier, Oliver (2018)
Zusammenfassung: On 27 June 2018, the majority of Chemical Weapons Convention (CWC) States Parties adopted a decision to expand the mandate of the Organisation for the Prohibition of Chemical Weapons (OPCW). The additional tasks include providing information on who is using chemical weapons in Syria. The decision was adopted by majority vote. It paves the way for The Hague-based organisation to later identify or, at least, create the conditions for the identification of those responsible for chemical weapons attacks. It also strengthens chemical weapons control because the OPCW will now hopefully be able make reliable statements on who is responsible for the continuing use of chemical weapons. However, it also risks politicising the Technical Secretariat and is likely to further complicate preparations for the CWC’s Fourth Review Conference, taking place from 21–30 November 2018